Variability in the Response of Bacterial Community Assembly to Environmental Selection and Biotic Factors Depends on the Immigrated Bacteria, as Revealed by a Soil Microcosm Experiment - Xiaogang Wu (American Society for Microbiology, 2019)
ABSTRACT Exploring the assembly mechanism of microbiota is critical for understanding soil ecosystem functions. However, the relative importance of different biotic and abiotic factors in determining the bacterial community has not been properly clarified. In this study, the effects of inocula and recipients on the assembly of the soil community were investigated to evaluate their importance by inoculation experiments with sterile soil. Two distinct soils, conventional nitrogen-fertilized soil and aromatic-compound-contaminated soil, were sterilized, cross inoculated, and incubated for 2 months under different inoculation doses and oxygen conditions. The results showed that the greatest variation in community structure emerged in the samples inoculated with distinct inocula rather than in the samples of different soil recipients. The phylogenies in the two inocula were diverse and dissimilar, although there were many ecologically equivalent bacteria. When the inocula with dissimilar ecologically equivalent species were used, the assembled communities were primarily determined by the inocula as indicated by the beta diversity and variation partitioning analyses. In contrast, environmental selection dominated the process when ecologically equivalent species in the inocula were similar, as when only one type of inoculum was used, where the soil habitat selected the most adaptive bacteria from the defined inoculum pool. These results indicate that inoculated bacteria are dominant over environmental selection if they are sufficiently dissimilar, although the effect of environmental selection is more obvious when similar bacteria are inoculated in the soil for community assembly. Our findings suggest that the immigration of exotic bacteria could be a primary factor impacting community assembly. IMPORTANCE The soil microbiota conducts important biological ecosystem functions, but the mechanism underlying community-environment interactions for soil microbiota remains unclear. By using two distinct soils for cross inoculation, we successfully simulated the assembly of the bacterial community in sterile soil. Thus, the reasons why inoculum and recipient have dominated community assembly in previous investigations are investigated in this study. We found that inoculated bacteria presided over environmental selection for community assembly due to the varied difference of ecological equivalent bacteria, either divergent or convergent. The significance of neutrality for the ecologically equivalent bacterial species that immigrated into the recipients should be emphasized in exploring the mechanisms of community assembly. Our finding is helpful for understanding the community-environment interaction, a basic question in ecology, and it would shed light on this issue that has perplexed scientists for many years.